Bonjour,
Factoriser:
A= (x+2)(2x- 1)+(x+2)(3x+2)= (x+2)(2x-1+3x+2)= (x+2)(5x+1)
B = x(x-2)+(x−2)(x + 2)= (x-2)(x+x+2)= (x-2)(2x+1)= 2(x-2)(x+1)
C = 3(2 + 3x) - (5 + 2x) (2 + 3x)= (2+3x)(3-5-2x)= (2+3x)(-2x-2)= -2(3x+2)(x+1)
D = (5x - 3)(x-7)(2x + 4)(x-7)= (x-7)² (5x-3)(2x+4)= 2(x-7)²(5x-3)(x+2)
E = (4x - 3)(7-3x) + (4x - 3)²= (4x-3)(7-3x+4x-3)= (4x-3)(x+4)
F = (2-5x)² - (2-5x)(1+x)= (2-5x)(2-5x-1-x)= (2-5x)(-6x+1)= (5x-2)(6x-1)
G = (2x + 1)(x − 3) + (2x + 1)= (2x+1)(x-3+1)= (2x+1)(x-2)
H = 5(1-2x) - (4 + 3x) (2x - 1)= -5(2x-1) - (4 + 3x) (2x - 1)= (2x-1)(-5-4-3x)
= (2x-1)(-3x-9)= -3(2x-1)(x+3)